Uji Aktivitas Antidiabetes dari Ekstrak Metanol Buah Kiwi (Actinidia deliciosa) melalui Penghambatan Aktivitas α-Glukosidase: Antidiabetic Activity of Kiwi Fruit (Actinidia deliciosa) Extract through Inhibition of α-Glucosidase Activity - Okpri Meila; Noraini Noraini (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
Diabetes melitus (DM) is defined as a chronic metabolic disease or disorder with multiple etiologies characterized by high blood sugar levels. One way to treat diabetes mellitus is inhibiting the α-glucosidase enzyme. This study aims to determine the inhibition of α-glucosidase of methanol extract of kiwi fruit (Actinidia deliciosa) . Kiwi fruit (Actinidia deliciosa) contains saponins characterized by the formation of foam, positive flavonoid characterized by the formation of a yellow color (orange) and positive alkaloid which is characterized by brown color in wagner test. The inhibition activity test of α-glucosidase enzyme was performed by using spectrophotometric method. The results of the inhibition activity test of α-glucosidase enzyme in acarbose showed the value of 13,672 mg/L, while the methanol extract of kiwi fruit showed IC50 value of 7.219 mg/L. It demonstrated that themethanol extract of kiwi fruit has the inhibition activity greater than acarbose.